Macrophage-mediated mechanisms of lung injury in the sensitization reaction to Echinococcus granulosus - Li, Yu-qian; Wang, Chun-sheng; Zhou, Jing-ru; Wang, Jia-ling; Tailaiti, Subi; Lin, Jia-ying; Bayina, Batesurong; Cao, Li-wei; Ye, Jian-rong (Frontiers in Immunology, 2024)
Objective: In this study, the impact of inhibiting the PI3K/AKT/NF-κB pathway on lung oxidative damage induced by Echinococcus granulosus cyst fluid was investigated. Methods: Twenty-four mice were randomly assigned to four groups. Three months after inoculation with hydatid cyst segments, mice in group A were treated with intraperitoneal and intratracheal saline injections; mice in group B were administered a caudal vein injection of a PI3K inhibitor, followed by cyst fluid sensitization; mice in group C received an AKT inhibitor via caudal vein, followed by cyst fluid sensitization; and mice in group D were subjected to cyst fluid sensitization without any inhibitor treatment. Cellular changes in lung tissues across all groups were evaluated, including pathological section analysis. Analysis of pulmonary tissue and serum from these mice included the assessment of PI3K/AKT/NF-κB pathway proteins, inflammatory factors, and related mRNA levels. Results: Mice in groups B and C exhibited a higher proportion of M2-type macrophages and significantly lower levels of PI3K/AKT/NF-κB pathway proteins, inflammatory factors (interleukin-6 [IL-6]/tumor necrosis factor-α [TNF-α]), and oxidative markers in lung tissues compared to mice in group D (P < 0.05). Conclusion: Our results in this study indicate that activation of the PI3K/AKT/NF-κB pathway contributed to an increase in the M1 macrophage phenotype, leading to enhanced secretion of peroxidases and inflammatory factors. This mechanism plays a crucial role in the oxidative and inflammatory lung damage associated with allergic reactions to E. granulosus cyst fluid.